Uji Sitotoksik Ekstrak Etanol Daun Stevia (Stevia Rebaudiana Bertoni) pada Kultur Sel Hela - Ghani Nurfiana Fadma Sari; Endang Sri Rejeki (Jurnal Farmasi Indonesia, 2021)
In Indonesia cervical cancer ranks second after breast cancer experienced by women. Stevia is a shrub that is used as a low-calorie sweetener. Stevia also has bioactive compounds such as steviosida, alkaloids, tanin, steroid and flavonoid which are useful as a treatment. Stevia leaf research as an anticancer has not been done much. Therefore, research on the cytotoxic effects of stevia leaves on HeLa cells. The purpose of this study was to determine the IC50 value of stevia leaves on HeLa cells. Stevia leaf extraction was carried out by maceration method using 96% ethanol solvent. The ethanol extract of stevia leaves was tested for its effect on HeLa cells using the MTT method with a concentration series of 500; 250; 125; 62.5; 31.25; 15,625 µg / mL. Cisplastin (Kalbe) is used as a positive control and cell control as a negative control. The results of testing the cytotoxic activity of stevia leaf ethanol extract on HeLa cells showed an IC50 value of 512.94 ± 1.62 µg / ml and IC50 value of Cisplatin 16.16 ± 1.75 µg / ml. This shows that ethanol extract of stevia leaves can be used as a cancer chemo preventive agent that acts to prevent the development of cancer cells